Neuroimaging markers of phenomena of perceived stigmatization in people with and without mental disorders: a systematic scoping-review - Natalia B. Lutova; Maria A. Khobeysh; Ekaterina S. Gerasimchuk; Maria O. Bocharova; Olga V. Makarevich; Mikhail Yu. Sorokin (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
Summary. Along with traditional research on psychiatric stigma, there has recently been increasing interest in the neurobiological factors associated with stigmatization.Aim: to study the most common research methods in the studies of the neurobiological correlates of stigmatization phenomenon and its components, as well as to systematize their results, taking into account their methodological limitations.Materials and Methods: The review was conducted in accordance with the PRISMA-ScR extension. Studies were searched in MEDLINE, EMBASE, PsycINFO using the Ovid platform. After evaluating 2358 articles according to inclusion, non-inclusion, and exclusion criteria, 20 articles were included in the final analysis.Results: The most of the studies were conducted on samples of healthy respondents without a control group (14 articles). The mean age of respondents ranged from 18.8 [1.0] to 42.7 [14.7] years. Psychiatric stigma was studied in 2 studies; in the remaining articles, various components of stigma were studied, among which social rejection sensitivity was most often studied (13 articles). Among fMRI paradigm the Cyberball social exclusion task was used more often (10 articles). Changes in neural activity, correlating with the severity of stigma and its constituent constructs, were found in the anterior cingulate cortex, prefrontal cortex, insula, thalamus, hypothalamus, hippocampus, parahippocampal gyrus, ventral region of the striatum, putamen, amygdala.Conclusion: Functional magnetic resonance studies can be an effective tool for verifying and assessing the dynamics of the psychological state of people experiencing the phenomenon of stigmatization.